2022
DOI: 10.2174/1573406417666210806094543
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel 2-imino-4-thiazolidinones as Potential Antitumor Agents for Glioblastoma

Abstract: Aims: The purpose of our study was to explore the molecular hybridization between 2-imino-4-thizolidione and piridinic scaffolds and its potential antitumor activity. Background: Glioblastoma is the most aggressive glioma tumor clinically diagnosed malignant and highly recurrent primary brain tumor type. The standard of treatment for a glioblastoma is surgery, followed by radiation and chemotherapy using temozolomide. However, the chemoresistance has become the main barrier to treatment success. 2-imino-4-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
4
0
2
Order By: Relevance
“…Interestingly, PC3 cells were found more susceptible than MDMB-231 cells against these agents. Of these derivatives, thiazolidine 2,4-dione containing indole or azaindole scaffolds (12,13,16,25) found to be more potent than thiazole-thiazolidine 2,4-dione hybrid (7). Particularly, molecular hybridization of thiazolidine 2,4-dione with N-2-(4-(trifluoromethyl)phenyl)ethanol and azaindole (compound 16) was the most effective among the series resulted in potent antiproliferative activity toward both PC3 and MDMB-231 cell lines with IC 50 4.28 μM and 2.5 μM, respectively.…”
Section: In Vitro Antitumor Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, PC3 cells were found more susceptible than MDMB-231 cells against these agents. Of these derivatives, thiazolidine 2,4-dione containing indole or azaindole scaffolds (12,13,16,25) found to be more potent than thiazole-thiazolidine 2,4-dione hybrid (7). Particularly, molecular hybridization of thiazolidine 2,4-dione with N-2-(4-(trifluoromethyl)phenyl)ethanol and azaindole (compound 16) was the most effective among the series resulted in potent antiproliferative activity toward both PC3 and MDMB-231 cell lines with IC 50 4.28 μM and 2.5 μM, respectively.…”
Section: In Vitro Antitumor Activitymentioning
confidence: 99%
“…For that purpose, thiazolidine 2,4-dione skeleton has been extensively utilized to obtain novel anticancer agents [11][12][13]. For instance, combination of 2,4-thiazolidinone with privileged scaffolds (Figure 1) such as pyrazole (I) [14], thiazole (II) [15], pyridine (III) [16], quinoline (IV) [17], coumarin (V) [18], and indole (VI) [19] led to potent anticancer activities against numerous cell growths. Further studies toward mechanism of action indicated that most of these privileged scaffolds-thiazolidine 2,4-dione hybrids exerted variety of mechanism such as potent inhibitors of VEGFR2-tyrosine kinases [13], apoptosis inducers through caspase-dependent pathways [16], and inhibition of carbonic anhydrases [17] as well as tubulin polymerization [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В настоящий момент основным цитостатиком, используемым для лечения таких больных, остается темозоломид. Исследования химио-и радиорезистентности клеток глиомы к этому препарату под воздействем реактивных астроцитов весьма ограниченны [45,[50][51][52][53].…”
Section: резистентность глиом: каков вклад реактивных астроцитов?unclassified
“…The molecular hybridization approach was applied for the synthesis of pyridine–4-thiazolidinone hybrids with aim of the synthesis of potential antiglioblastoma agents by Campos et al [ 50 ]. Among sixteen synthesized compounds, derivatives 50–52 ( Figure 20 ) displayed potent antitumor activities against the tested glioblastoma cell lines and exhibited IC 50 values 2.17, 6.24, and 2.93 μM, respectively, in the C6 cell line, well below the standard drug temozolomide.…”
Section: Privileged Heterocyclic Scaffolds–4-thiazolidinones Hybrid M...mentioning
confidence: 99%